Removal of iron and oil from palm oil mill effluent using chitosan coated alginate–mangrove composite beads - Jawad, Rana Jaafar (2016)
This research focuses on the removal of iron ions and residue oil from palm oil mill effluent using chitosan-coated alginate–mangrove composite beads (CCAMCB). The Fourier transforms infrared spectroscopy (FTIR) was used to reveal the main functional groups and to prove the successful coating of beads by chitosan, and scanning electron microscope (SEM) with energy dispersive X-ray spectroscopy (EDX) and swelling studies were employed to discover the surface morphology, chemical composition and identify the crystalline nature of the beads, respectively. The adsorption process was conducted through batch studies and continuous studies. In batch studies, the influence of different experimental parameters such as pH, adsorbent dosage, contact time, and initial concentration on iron ions and residue oil removal was investigated to determine the optimum operating conditions. The results of the batch studies reveal that the maximum removal of iron ions was 92.7% at pH 3, 300 g/L of adsorbent concentration, and contact time of 72 hours, and the maximum removal of residue oil was 98.47% at pH 3, 50 g/L of adsorbent concentration, and contact time of 2.5 hours. The adsorption isotherm studies reveal that both iron ions and residue oil followed the Freundlich isotherm model, and in terms of kinetic studies, both iron ions and residue oil followed the pseudo second order. Continuous studies were performed in a fixed bed column with different bed heights, and it was found that the time of breakthrough increased with a higher bed depth. The Thomas model and Yoon-Nelson model were used to estimate the experimental data. As a conclusion, the CCAMCB demonstrated a potential application to remove iron ions and residue oil from POME.